2015
DOI: 10.1080/15384047.2015.1026506
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiation therapy of renal cancer inferior vena cava tumor thrombus

Abstract: Renal Cell Carcinoma (RCC) is a common malignancy world-wide that is rising in incidence. Up to 10% of RCC patients present with inferior vena cava (IVC) tumor thrombus (IVC-TT). Although surgery is the only treatment with proven efficacy for IVC-TT, the surgical management of advanced (level III and IV) IVC-TT is difficult with high morbidity and mortality, and offers a poor survival outcome. Currently, there are no treatment options in the setting of recurrent or unresectable RCC IVC-TT. Even though RCC may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
(46 reference statements)
1
18
0
Order By: Relevance
“…We previously reported a 24month follow-up of this patient with a reduction in size and enhancement of the tumor thrombus, despite no additional systemic therapy ( Fig. 1D) [11]. After a follow-up of an additional 10 months, the patient developed left proximal femur and multiple liver metastases.…”
Section: Case Descriptionmentioning
confidence: 70%
See 1 more Smart Citation
“…We previously reported a 24month follow-up of this patient with a reduction in size and enhancement of the tumor thrombus, despite no additional systemic therapy ( Fig. 1D) [11]. After a follow-up of an additional 10 months, the patient developed left proximal femur and multiple liver metastases.…”
Section: Case Descriptionmentioning
confidence: 70%
“…We report an update on our initial experience with SBRT to RCC IVC-TT, the first such experience reported in the literature, providing an extended follow-up [11] and a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Another unique application of SABR in RCC is targeting inferior vena caval tumor thrombus (IVCTT). Hannan et al [56] have demonstrated this to be feasible and tolerable, with encouraging oncological results in a recent case series. Given the high-risk nature of thrombectomy surgery, SABR may thus be an option for patients with unresectable or recurrent IVCTT.…”
Section: Novel Applications Of Renal Sabrmentioning
confidence: 92%
“…One is a case report of intensity-modulated radiotherapy (56 Gy/24 fractions of one fraction per day) that stabilized a tumor embolus in clear cell RCC [7]. Another is the only existing report of SRT for IVC tumor thrombus of RCC by Hannan et al, which showed only partial remission at two years follow-up and 18-month survival [8].…”
Section: Discussionmentioning
confidence: 99%